Human resource management : gaining a competitive advantage - Noe, Raymond A.; Hollenbeck, John R.; Gerhart, Barry A. (New York McGrawhill, 2021)
"Our intent is to provide students with the background to be successful HRM professionals, to manage human resources effectively, and to be knowledgeable consumers of HRM products. Managers must be able to identify effective HRM practices to purchase these services from a consultant, to work with the HRM department, or to design and implement them personally. Hu-man Resources Management: Gaining a Competitive Advantage, 12th edition, emphasizes how a manager can more effectively manage human resources and highlights important issues in cur-rent HRM practice"--
Revised edition of Human resource management, 2016.
Includes index.
Keywords: Personnel management -- United States